Effect of Long Term Excessive Zn Supplementation on Blood Lipid Profile and Tissue Minerals Status in Wistar Rat - S.K. Taneja2, K.B. Singh1* and (Journal of Experimental Sciences, 2010)
During the last two decades the amount of Zn consumed from Zn-fortified foods and Zn rich dietary supplements have doubled for all age groups and the amount of this will further increase over time. The effect of long term increasing Zn load in the blood lipid profile and tissue minerals status in the body has not been worked out so far. In this study, three groups of rats were fed on semi-synthetic diet containing 20 mg Zn/kg (control, group-I), 40mg Zn/kg (group-II) and 80mg Zn /kg (group-III) diet respectively for a period of 180 days. The results revealed that the gained in body weight increased in rats in Zn concentration dependent manner. The blood lipid profile displayed a significant rise in serum total lipids, cholesterol, triglycerides, LDL-cholesterol, VLDL- cholesterol whereas HDL-cholesterol showed a reduction in their levels in group-II and III than their control counter parts. The tissue metal status showed an increase of Zn, Cu, Mg and Mn in the serum, a rise in Zn in liver and kidney and fall in Cu, Mg and Mn in kidney and liver. This data suggest that excess Zn in diet when fed for longer periods of time alter blood lipid metabolisms and tissue minerals status. ——————————————————————————————————– 1Department of Zoology, PUC, Mizoram University, 796001, India; 2Department of Zoology, Panjab University, Chandigarh, 160014, India * Corresponding Author, Email: birla.kshetri@gmail.com Please Cite This Article As: K.B. Singh and S.K. Taneja. 2010. Effect of Long Term Excessive Zn Supplementation on Blood Lipid Profile and Tissue Minerals Status in Wistar Rat. J. Exp. Sci. 1(3): 4-9.